Negrafias no centro de São Paulo: a presença e a representação do negro na arte urbana - Barbosa, Marina Oliveira [UNIFESP] (2019)
Brazil it's a multiracial and multi-ethnic country where more than half the population identify themselves as black or brown. Yet, this majority isn't visible, for example, on media – advertising, tv shows and journalistic programs – neither have expressiveness, in a minimal equal way, on other cultural sections – as cinema, theater – and social, above all in professions of great visibility as politics, judiciary, legislative, executive and etc. One of the first elements for self-affirmation of blackness goes through revaluation and through recognition of its own image, both individual and collective. The graffiti has been one mean of expression and one way of affirmation of that image in São Paulo's city, as graffiti artists incorporate to their repertory racial and black ethnics to show their social visibility/invisibility, build and enrich their black cultural identity. The present work looks to map and analyse the presence of the image of black men and women in graffiti – on negrafias¹ – found on specific routes through São Paulo's city, paying attention to one possible reconfiguration and appropriation of space as the democratization of it. This route belongs to the author – student and worker. Therefore, based on this ethnographic case study the dissertation will offer an analysis of the presence and representation of black women and men in negrafias2 , asking if it could reconfigurate a city willing itself as white. Therefore, it's about a work that brings to Art History an anthropologic and ethnographic methodology proposal, since the cut isn't based exclusively on the work's concept of art or the study of chosen artists, but also of experiencing the city through a route considered mutual, but in a subjective point of view.